Minding the child’s mind: parental reflective functioning as a buffer for child distress in displaced families at war zones - Enav, Yael; Mayer, Yael (Frontiers in Psychology, 2025)
BackgroundDespite being an exceptionally vulnerable group, internally displaced children are underrepresented in the literature. Parents are instrumental in providing support to these children.ObjectiveThe aim of this study is to investigate the moderating role of perceived parental reflective functioning (PRF) in the relationship between parental war exposure, parental stress, and parent-rated child distress.Participants and methodNinety-six internally displaced Israeli families with young children ages 3–6 were involved. Data was gathered online through online questionnaires using Qualtrics. Parents completed self-report measures assessing their exposure to war-related events, levels of stress and depression (Depression and Anxiety Stress Scale), child distress (Child Stress Scale), and PRF (Parental Reflective Functioning Questionnaire).ResultsParental reflective functioning (PRF) moderated the indirect link between parental war exposure and parental ratings of child distress via parental stress. At low and moderate PRF, parental stress fully mediated this relationship (Moderate: indirect = 0.05, p < 0.05, 95% CI [0.01, 0.09]; Low: indirect = 0.09, p < 0.05, 95% CI [0.02, 0.17]). At high PRF, the indirect effect was non-significant, and a direct association emerged (b = 0.11, p = 0.007), suggesting that highly reflective parents may be more directly attuned to children’s emotional responses to war exposure.ConclusionThese findings highlight the protective role of PRF in war and support the development of PRF-enhancing interventions to promote resilience among young, internally displaced children.